18.ANALYSIS OF REPORTING OF THE ISSUANCE OF GOOD DISTRIBUTION PRACTICE CERTIFICATES IN VIETNAM DURING THE PERIOD OF 2020-2022 (Vietnam Journal of Community Medicine, 2025)
Objective: Analyzing the implementation and reporting the issuance of Certificates of GDP for drug wholesalers by the Department of Health nationwide based on Circular 03/2018/TT-BYT.Subjects and methods: The cross-sectional descriptive study was conducted based on data sources taken from three sources including the Pharmaceutical Business and Practice data management software (according to Official Dispatch 14028/QLD-KD), Electronic document management and administration system - Ministry of Health (according to Official Dispatch 8027/QLD-KD) and Electronic Information Portal of the Department of Health.Results: The results showed that according to Official Dispatch 14028/QLD-KD, the number of drug wholesalers meeting GDP reported from 2020-2022 was 136, 51 and 49 wholesalers respectively. The Department of Health's reporting according to Official Dispatch 8027/QLD-KD was insufficient, of which 20 provinces, cities did not have data reporting on the issuance of GDP Certificates. The number of facilities meeting GDP in 2021 reported by the Departments of Health according to Official Dispatch 14028/QKD-KD had a big difference with the data reported according to Official Dispatch 8027/QLD-KD. All Departments of Health published inadequately information about facilities that met GDP on the Department's Electronic Information Portal for the 3 years 2020-2022.
Keywords: Good distribution practice; drug wholesaler